Looking ahead from age 6 to 13: A deeper insight into the development of planning ability. (13th January 2014) - Unterrainer, Josef M.; Kaller, Christoph P.; Loosli, Sandra V.; Heinze, Katharina; Ruh, Nina; Paschke‐Müller, Mirjam; Rauh, Reinhold; Biscaldi, Monica; Rahm, Benjamin
<x xml:space="preserve">Abstract</x> Planning ability gradually increases throughout childhood. However, it remains unknown whether this is attributable to global factors such as an increased ability and willingness to inhibit premature, impulsive responding, or due to the availability of specific planning operations, such as being able to mentally plan ahead more steps ('search depth') or to derive a clear temporal order of goals by the task layout ('goal hierarchy'). Here, we studied the development of planning ability with respect to these global and problem‐specific aspects (search depth and goal hierarchy) of performance in 178 children from 6 to 13 years using the Tower of London task. As expected, global performance gradually developed with age. In accordance, planning durations increasingly reflected global problem demands with longer pre‐planning in harder problems. Furthermore, specific planning parameters revealed that children were increasingly capable of mentally searching ahead more steps. In contrast, the ability to derive a goal hierarchy did not show age‐related changes. While the global development of planning performance and adaptive planning durations were proposed to primarily reflect enhanced self‐monitoring, the specific increase in search depth across childhood that most likely proceeds until young adult age represents more directly planning‐related processes. Thus, development of planning ability is supported by multiple contributions.